STRATEGI ELIT LOKAL MEMBANGUN WACANA PEMEKARAN (Studi Kasus Wacana Pemekaran Provinsi Bolaang Mongondow Raya) - , Abdillah Umbola, Nur Azizah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to see the strategy applied by the ruling local government to realize territorial expansion draft. Ever since the idea of territorial expansion was proposed to the public of Bolaang Mongondow Raya (BMR), there has not been any contending ideas. In order to realize this draft, the local government has to have strategy, as well as assets (Economic asset, cultural asset, symbolic asset) if they would want it to be a dominant, prioritized draft. According to Bourdieu, a possible strategy that ruling government could take in order to make a draft dominant is through conservation, which is an act of defending and building upon the established drafts. The assets mentioned above then could be used by the ruling government to massively produce or reproduce the idea of the said drafts so it becomes imprinted as public opinion. Thus, the society upon which the imprinted draft âlivesâ as public opinion becomes unconsciously controlled by the government. The research questions of this study is what is the strategy (how to do it) of the ruling government of Bolaang Mongondow Raya in consolidating the territorial expansion draft? This study utilizes descriptive-qualitative method with case study approach. By such method, the reason behind the popularity of territorial expansion could be explained. The approach of this study has the purpose of explaining such phenomenon intensively, thoroughly, and detailed. The data analysis utilizes triangulation technique. The data consists of primary and secondary data whose validity is gathered, analyzed, and verified. Based on the research, two dominant issues concerning the territorial expansion draft are identified: (1) the issue of prosperity (visible)